ANALISIS BIAYA MAKAN DAN BIAYA SISA MAKANAN PADA PASIEN DI RUMAH SAKIT ( LITERATUR REVIEW ) - Dyah Octavia Rizky; Ida Ayu Eka Padmiari; Ni Nengah Ariati (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2023)
Food cost is the cost required to provide food which is obtained based on the total costs incurred divided by the number of servings of food and the number of consumers served. Food waste is the number of dishes that are not eaten, which occurs because the leftovers served are not consumed. The food waste costs is calculated by knowing the amount of food waste from the patient and then compared with the cost of food per serving. The purpose of this study was to analyze of food cost and food waste cost in hospitalized patients. The independent variable in this study is food cost and the dependent variable is food waste cost. This research is a literature review conducted in May 2021 by searching the database on Google Scholar and Research Gate then classifying the literature according to inclusion criteria and analyzing it based on existing theory. The research subjects are patients who are hospitalized, male and female, with an age range of 0-65 years. The research data includes subject criteria (gender, age), food costs, food waste and food waste cost of patients in hospital. Based on the results of the literature review, there are 4 literatures of food cost, the lowest is in the VIP Room of RSJ Prof. Dr. Soerojo Magelang is Rp. 21,634,- while the highest is in Class III Inpatient at the Mataram City Hospital of Rp. 70,366,-. There are 7 literatures that show of food waste in hospitalized patients, the average food waste is 58.25% with the highest is 100%. There are 5 literatures that describe food waste cost with the highest is Rp. 560,000,- in Sidoarjo City Hospital and the lowest is Rp. 9,530, - in schizophrenia patients at Prof.. Dr. Soerojo Magelang Psychiatric Hospital. There are 4 literatures that state the relationship between food costs and food waste costs.Keywords: food costs, food waste and food waste costs